NEW SYSTEM IN CRIMINAL PROCEEDINGS AGAINST VILLAGE HEADS FOR CORRUPTION OF VILLAGE FUNDS - Surya Hamdani; Saritua Silitonga; Sarah Furqoni; Muhammad Dhobit Azhary Lubis (Jurnal Scientia, 2023)
Decision number 168 k/pid.sus/2018 on behalf of the defendant kabul santosa bin wito diharjo was proven legally and convincingly guilty of committing the crime of "corruption", sentencing the defendant therefore to imprisonment for 4 (four) years and a fine of Rp200,000,000.00 (two hundred million rupiah) provided that if the fine is not paid it will be replaced by imprisonment for 6 (six) months, imposing additional punishment on the defendant to pay compensation of Rp124. 995,925.00 (one hundred twenty-four million nine hundred ninety-five thousand nine hundred twenty-five rupiah) which is compensated or calculated with the money confiscated by the public prosecutor in the amount of Rp124,995,925.00 (one hundred twenty-four million nine hundred ninety-five thousand nine hundred twenty-five rupiah). The purpose of this study is to examine the criminal act of corruption of village funds committed by the village head of Bunder and examine the judge's consideration in deciding the case of criminal acts of corruption of village funds committed by the village head and examine the accountability of the village head who committed criminal acts of corruption of village funds.